Pharmacokinetics, efficacy and toxicity of parenteral halofantrine in uncomplicated malaria. - Krishna, S; ter Kuile, F; Supanaranond, W; Pukrittayakamee, S; Teja-Isavadharm, P; Kyle, D; White, N (1993)
1 The pharmacokinetics, efficacy and toxicity of a new parenteral formulation of halofantrine hydrochloride were evaluated in 12 adults with acute uncomplicated falciparum malaria and nine adults who attended in convalescence. 2 Intravenous halofantrine (1 mg kg(-1) infused in 1 h) was given every 8 h for a total of three doses in the acute study. Halofantrine cleared parasitaemia rapidly in all but one patient, with a mean (s.d.) parasite clearance time of 71 (29) h. Convalescent patients received a single infusion (1 mg kg(-1) in 1 h). 3 An open two-compartment model with the following parameters described the pharmacokinetics of halofantrine in acute malaria (mean (s.d)): V1 = 0.36 (0.18) l kg(-1); CL = 0.355 (0.18) l h(-1) kg(-1); t1/2alpha = 0.19 (0.12) h; t1/2beta = 14.4 (7.5) h. 4 Intravenous halofantrine in acute malaria produced significant prolongations of the QT and QTc intervals (mean (s.d.)) of 20 (15%) and 8.2 (5.6)%, respectively (P < 0.001) after the third dose, but no clinically significant cardiotoxcity. Eight patients experienced mild to moderate thrombophlebitis at the halofantrine infusion site which had resolved in six by the time of follow-up. In the single treatment failure who received oral quinine, there was a large rise in plasma halofantrine concentration but this did not result in detectable toxicity. 5 These data provide the basis for the design of improved dosing regimens for the use of parenteral halofantrine in malaria.